Respuesta de la frecuencia cardiaca de anticipación y recuperación en función del nivel de entrenamiento aeróbico - Zamorano, V. G.; Peinado, A. B.; Benito, P. J.; Calderón, F. J. (Archivos de medicina del deporte, 2013)
Introduction: Heart rate (HR) is considered a fundamental parameter to assess the intensity of an exercise and prescribe training loads appropriate for increased physical performance. Objectives: To compare the variation in anticipatory and heart rate recovery in the fi rst minute during a maximal exercise test, between two diff erent groups of subjects with diff erent aerobic training levels. Material and methods: It was carried out a maximal test using a cycle ergometer, with 66 elite cyclists and 51 sport sciences students. Their heart rate was recorded throughout the test and it was calculated the anticipatory and heart rate recovery at 20 s, 30 s and 1 min of the fi rst warm-up minute and recovery. Student`s t-test for independent samples and repeated measures ANOVA were used with statistical signifi cance at the 5% level. Results: Cyclists had a better anticipatory heart rate for the fi rst 30 s (cyclists vs. students: 6.3±12.2 vs. 10.3±12.9 beats x min-1, p<0.05), having better heart rate recovery 30 s after fi nishing exercising as well (cyclists vs. students: 20.2±8.3 vs. 16.0±10.3 beats x min-1, p<0.05). Similarly, the slope of the FC recovery was greater than anticipatory of heart rate (except for second 20), independent of the training level. Also, it was observed the non-linear anticipatory heart rate against FC recovery always linear. Conclusions: The anticipatory heart rate (FCant) and recovery (FCrec) was related to the aerobic level and it may be a good indicator of cardiovascular adaptation.